Characterization and host range assessment of Dickeya zeae associated with pineapple soft rot disease in East Lampung, Indonesia - Titik Nur Aeny; Radix Suharjo; Cipta Ginting; Dwi Hapsoro; Ainin Niswati (Society for Indonesian Biodiversity, 2020)
Abstract. Aeny TN, Suharjo R, Ginting C, Hapsoro D, Niswati A. 2020. Characterization and host range assessment of Dickey zeae associated with pineapple soft rot disease in East Lampung, Indonesia. Biodiversitas 21: 587-595. The study aims to characterize the Dickeya zeae associated with pineapple soft rot in East Lampung, Indonesia and to assess the bacterial host range. From the blister-like lesion-symptom, bacteria were isolated with the morphological characteristics: circular, convex, cream white milk-colored, with diameter colonies ranging from 1-2 mm in diameter. Two strains (N-Unila 5 and N-Unila 10) were selected for further investigation including pathogenicity test on pineapple seedling, species identification by phenotypic characteristics and molecular techniques using sequence analysis of 16SrDNA, recA, and dnaX as well as host range test on 25 different plant species. The result of the pathogenicity test showed similar symptoms to those observed in the field. Physiological and biochemical characterization revealed that the two isolates were Gram-negative bacteria, fermentative, lecithinase positive, non-fluorescent on King’s B medium, able to grow on YDC medium at 41oC, did not produce H2S and did not grow in the presence of 5% NaCl. The isolates capable of using Myo-inositol, M-tartrate, mannitol, L-tartrate, lactose, glycerol, D-melibiose, D-arabinose, citrate, and cis-aconitic acid but did not utilize starch, S-ketoglucanate, L-ascorbic acid, inulin, folic acid, D-raffinose and tartrate as a sole carbon source. Phenotypic characteristics indicated that the strains were in the group of Dickeya spp. bv. 3 (phenon 1). Sequence analysis of 16S rDNA, recA, and dnaX revealed that the strains were placed in the same cluster with the reference strain of D. zeae. Host range assessment showed positive soft rot symptoms in Aloe vera, chinese cabbage, dragon-fruit, eggplant, lettuce, and welsh onion that have never been reported before.